BIOGRAFI BUYA HAJI ABDUL SALAM IMAM SEBAGAI TOKOH AGAMA ISLAM DI DHARMASRAYA SUMATERA BARAT (1968-2005) - Herlina, Herlina; Nazmi, Ranti; Kaksim, Kaksim (Pendidikan Sejarah, 2014)
Buya Haji Abdul Salam Imam is Islamic religious leaders who started spread of Islam in Dharmasraya. Armed with knowledge gained from the Islamic boarding school and some general science at MTI Bukittinggi, then he started doing the spread of Islam, athoungh just with the simple method. In 1968 he founded the first of Islamic boarding school in Pulai village Sitiung the district. Until the end of his life, he has set up three boarding schools, the name is Pondok Pesantren Pulai, Pondok Pesantren Padang Laweh and Pondok Pesantren Sungai Duo Dharmasraya Sitiung. It has also been estabilished, namely formal education institutions Madrasah Tsanawiyah and Madrasah Aliyah. Spread of Islam done by Buya Haji Abdul Salam Imam begins with the conventional recitation eith the recitation sitting (halaqah). Up to the spread of modern managed.